2014
DOI: 10.1111/ejn.12566
|View full text |Cite
|
Sign up to set email alerts
|

Fixational saccades alter the gap effect

Abstract: The reaction times of saccadic eye movements have been studied extensively as a probe for cognitive behavior controlled by large-scale cortical and subcortical neural networks. Recent studies have shown that the reaction times of targeting saccades toward peripheral visual stimuli are prolonged by fixational saccades, the largest miniature eye movements including microsaccades. We have shown previously that the frequency of fixational saccades is decreased by volitional action preparation controlled internally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…We designed this model to provide the simplest possible explanation for the saccade abnormalities observed in ADHD. Recently Watanabe et al suggested that fixation saccades alter the gap effect, presumably by disrupting volitional saccade preparation [ 60 ]. However, an important limitation of this model is that it does not take into account execution signals for saccades, which may also be dysfunctional in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…We designed this model to provide the simplest possible explanation for the saccade abnormalities observed in ADHD. Recently Watanabe et al suggested that fixation saccades alter the gap effect, presumably by disrupting volitional saccade preparation [ 60 ]. However, an important limitation of this model is that it does not take into account execution signals for saccades, which may also be dysfunctional in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that individual differences in fixational saccades are correlated with those in antisaccade performance (Watanabe, Matsuo, Zha, MacAskill, & Kobayashi, ; Watanabe et al., ). Here, we extended the previous findings and identified relationships between antisaccade performance and ocular drift across subjects along with the other fixational eye movements.…”
Section: Resultsmentioning
confidence: 84%
“…Presumably, this is because early, high activity at the rostral pole is more likely to surpass threshold, and later, low activity is less likely to surpass threshold. It is unclear from this account why some subjects showed a rebound in microsaccade frequency in the middle of the warning period, although such rebounds have been reported previously (Watanabe et al 2014). Others have suggested that (micro)saccade production is controlled, in part, by an oscillatory rhythm, and stimuli onsets or offsets can reset this oscillator (Hafed and Ignashchenkova 2013).…”
Section: Microsaccades As a Dynamic Readout Of Sc Activity?mentioning
confidence: 89%
“…Other subjects displayed a decrease in microsaccade frequency that remained low throughout the remainder of the warning period. This variability may result, in part, from differences in subjects (Watanabe et al 2014), species (Martinez-Conde et al 2009), and warning-period durations, used here across species. Consistently, microsaccade frequency was lowest at the end of the respective warning periods, just before target presentation, suggesting that expected saccade timing influenced microsaccade generation (Hafed et al 2011;Pastukhov and Braun 2010).…”
Section: Microsaccade Frequency Was Modulated In Advance Of Saccadesmentioning
confidence: 99%
See 1 more Smart Citation